The Spain-NATO-United States Triangle: Who Controls the Negotiations? - Ford, Robert E. (Tufts Archival Research Center, 2005)
Volume 12, Issue 2. Summer Spain's role in NATO historically has been both ambiguous and heavily influenced by Spain's relations with the United States. Mutual defense agreements with the United States, multilateral negotiations with NATO and dramatic political changes in Spain have evolved along parallel tracks since the late 1940s. A triangular relationship has emerged recently, with each "leg" of the negotiations depending on the events in the others. Robert E. Ford analyzes how Spain-United States bilateral relations shape Spain's involvement with NATO.